PENGEMBANGAN USAHA KECIL dan MENENGAH (UKM) UNTUK PERCEPATAN PENINGKATA N EKONOMI DAERAH DI KABUPATEN INDRAGIRI HULU PROPINSI RIAU - Isjoni ' (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2003)
Society based economic program is seriously developed in Indragiri Hulu Regency.The program can increase and develop business environment, especially small and mediumenterprises (SME). In developing SME, there are some problems such as weakness of capitalstructure and access to capital resources; stocks and sustainability of raw material; limitedresources and technology achievement; weakness of organization and management; and lackof quantity and quality of human resources. An alternative solution is to encourage ruraleconomic institution that is cooperation. The cooperation has very important roles inencouraging economic of the societies especially in rural areas. Cooperation has to act as abusiness institution in rural areas and as executor to market SME’s products.